Effect of Cobalt Metal Insertion on Zinc Oxide Nanotube Structure for Hydrogen Gas Sensor Using Density Functional Theory Method - Ariyanti, Widia; Kasmui, Kasmui (Universitas Negeri Semarang, 2021)
Hydrogen gas as a renewable energy has limitations, namely flammable, explosive, colorless, and odorless, making it difficult to detect its presence at normal temperature and pressure. Efforts to determine the presence of hydrogen gas need a gas sensor. This study aims to determine the effect of the insertion of Co metal on Zinc Oxide nanotubes (ZnONT) on changes in adsorption energy and sensor sensitivity on H2 gas with parallel and perpendicular positions. Geometry optimization was carried out using the DMol3 module in Material Studio, the parameters of this research were using Density Functional Theory method, GGA correlation exchange PBE function, and DNP basis set. The results of the calculation of the hydrogen gas adsorption energy from the structures ZnONT.H2 perpendicular, ZnONT.H2 parallel, ZnONT.Co.H2 perpendicular and ZnONT.Co.H2 parallel, respectively, are -23.121205 kJoule/mol; -23.541810 kJoule/mol; -252.783422 kJoule/mol; and -254.599480 kJoule/mol. The calculation of the sensitivity of the hydrogen gas sensor response from the structures ZnONT.H2 perpendicular, ZnONT.H2 parallel, ZnONT.Co.H2 perpendicular and ZnONT.Co.H2 parallel were 1.374; 1,527; 1654,827; and 375,857. Based on the results of the study, it was found that the insertion of Co metal was able to increase the adsorption energy and sensitivity of the hydrogen gas sensor.